Twitter as a tool for agenda building in election campaigns? The case of Austria. (August 2019) - Seethaler, Josef; Melischek, Gabriele
During the 2017 Austrian national election campaign, political parties that had traditionally focused on press releases and conferences to influence the media's agenda made extensive use of Twitter for the very first time. This study examines the impact of the parties' Twitter campaigns on the substantive issue agendas of five leading legacy media outlets. Compared with the impact of parties' news releases, the results show that, on an aggregated level, Twitter feeds significantly increase the parties' agenda-building power, but are not influenced by the media agenda – with the exception of the personal accounts of the top candidates (particularly the new leader of the winning conservative party), who follow the media agenda to a significant extent. On an individual level, incumbent parties are the most successful in using Twitter, while small parties suffer from interactions with other parties in communicating their issue priorities (which is in line with the 'normalisation thesis').